Diversity Assessment and Cultivar Identification in Date Palm through Molecular Markers- A Review - Nadia Faqir; Aish Muhammad; Muhammad Zeeshan Hyder (Turkish Journal of Agriculture: Food Science and Technology)
Date palm has a long history of cultivation and a valuable germplasm with little knowledge about its genetic makeup and variation among the most cultivated cultivars. Diversity is the variability of a species. Plants show variation in yield, vegetative traits and morphological properties of fruits and seeds in response to environmental changes. Molecular markers or DNA markers have been in use since past three decades. The DNA profiles give information about the genotype, screen the whole genome and show variation in both the coding and noncoding region and hence give information about polymorphism. Since plastid genes are transferred mostly from the mother line, the identification of maternal lines is possible by the sequencing of plastid genes. Simple sequence repeats (SSRs) can detect length variation with the help of Polymerase Chain Reaction (PCR) and may be used as highly informative genetic markers. Single Nucleotide Polymorphism (SNPs) are the third generation of molecular markers. SNPs are more stable and have high fidelity of inheritance as compared to other marker systems. Molecular markers have been developed but they are not enough for sufficient diversity assessment. Therefore there is a need to increase the number of DNA markers in date palm. Previously, there are several studies to type various commercially important germplasm based on morphological or yield parameters. Morphological and biochemical markers are limited in number and are affected by environmental factors and growth stage of the plant which reduce their reliability in the assessment of diversity and characterization of the germplasm. This necessitates the use of genetic characterization, utilizing DNA markers, gene sequencing or SNP genotyping which can work independent of the plant growth stage and are not affected by environmental factors. A combination of morphological, biochemical and molecular characterization of the date palm cultivars can better assess the level of diversity and relationship among the cultivars.